The consequence of corona-virus (covid-19) on e-business in Pakistan - Waqas Ashraf, Muhammad; Khalid Latif, Dr.; Maqbool Khan, Qaisar; Jabbar, Jahangir (International Journal of Engineering and Technology, 2020)
This study investigates the consequences of Corona-virus (COVID-19) on the online business in Pakistan. COVID 19 changed the business world operations and procedures drastically. The new business norms evolved, and the human beings learned new practices for their behavior and business conduct. Developed nations like USA, UK, Italy suffered collapse of health care and economic activities. COVID-19 impacted all businesses including E-Business but the e-business is among few who got dual impact as most of the business activities are moving from physical to online that is e-business but due to the lock down e-businesses are not able to get the items on time. Small and medium enterprises (SMEs) and local business-es in Pakistan incurred huge losses due to the lock down and lack of facilities in developing countries like Pakistan. Some of the small-scale business permanently closed due to the COVID-19. E-Business also faces these terrible conditions in Pakistan due to the lack of government support and awareness. Many E-Commerce business imports product from China so that is the reason it is assumed that the Pakistani E-Business harshly effected by the COVID-19. This research survey shows that the COVID-19 has a negative impact on the e-Business in Pakistan.Â Â